Accumulation and distribution of heavy metals in surface sediments of a semienclosed basin in the southeastern Mediterranean Sea, Egypt - ABDALLAH, M.A.M. (Mediterranean Marine Science, 2007)
The distribution, enrichment and accumulation of heavy metals in the surficial sediments of the Alexandria City Eastern Harbour (Mediterranean coast of Egypt) were investigated. Surface sediments (in the <63mm fraction) collected from 12 sites representing the entire area of the harbour, were analyzed by AAS for Cd, Cu, Zn, Cr, Pb and Al. Metal contents were compared with literature data to assess the pollution status of sediments. Enrichment factors (EFs) and the geoaccumulation Index (Igeo) were calculated as a criterion of possible contamination.